Preliminary assessment of the Colombian import market - statistical annexes (The Company Santafe de BogotaCO, 1993)
Provides CARICOM exporters with the necessary information about the Colombian regulations concerning imports as well as with the market information which will allow them to assess the possibilities of the Colombian market.
DC